Both frontal and temporal cortex exhibit phonological and semantic specialization during spoken language processing in 7‐ to 8‐year‐old children. Issue 11 (5th May 2021) - Wang, Jin; Yamasaki, Brianna L.; Weiss, Yael; Booth, James R.
Abstract: A previous functional magnetic resonance imaging (fMRI) study by Weiss et al. (Weiss et al., Human Brain Mapping, 2018, 39, 4334–4348) examined brain specialization for phonological and semantic processing of spoken words in young children who were 5 to 6 years old and found evidence for specialization in the temporal but not the frontal lobe. According to a prominent neurocognitive model of language development (Skeide & Friederici, Nature Reviews Neuroscience, 2016, 17, 323–332), the frontal lobe matures later than the temporal lobe. Thus, the current study aimed to examine if brain specialization in the frontal lobe can be observed in a slightly older cohort of children aged 7 to 8 years old using the same experimental and analytical approach as in Weiss et al. (Weiss et al., Human Brain Mapping, 2018, 39, 4334–4348). One hundred and ten typically developing children were recruited and were asked to perform a sound judgment task, tapping into phonological processing, and a meaning judgment task, tapping into semantic processing, while in the MRI scanner. Direct task comparisons showed that these children exhibited language specialization in both the temporal and the frontal lobes, with the left posterior dorsal inferior frontal gyrus (IFG) showing greater activation for the sound than the meaning judgment task, and the left anterior ventral IFG and the left posterior middle temporal gyrus (MTG) showing greater activation for the meaning than the sound judgment task. These findings demonstrate that 7‐ to 8‐year‐old children have already begun to develop a language‐related specialization in the frontal lobe, suggesting that early elementary schoolers rely on both specialized linguistic manipulation and representation mechanisms to perform language tasks. Abstract : We designed an auditory sound judgment task tapping into phonological processing and an auditory meaning judgment task tapping into semantic processing. We found that 7‐ to 8‐year‐old children exhibited language specialization in both the temporal and the frontal lobes, with the left posterior dorsal inferior frontal gyrus (IFG) showing greater activation for the sound than the meaning judgment task, and the left anterior ventral IFG and the left posterior middle temporal gyrus (MTG) showing greater activation for the meaning than the sound judgment task. Our findings suggest that early elementary schoolers rely on both specialized linguistic manipulation and representation mechanisms to perform language tasks.